Design of a 2DOF parallel mechanism to assist therapies for knee rehabilitation (2016)
This paper presents a knee rehabilitation device to reproduce four exercises generally used in the rehabilitation therapies. The device consists of a mechanical structure based on a 2 DOF parallel mechanism, a controller with PIC-SERVO motion control boards, and a GUI that commands the device to reproduce the rehabilitation exercises. The position kinematic analysis of the mechanism is developed as well as its dimensioning synthesis to cover various leg sizes. This work proposes a technological alternative with significant advantages that responds to the global need for improving physical knee rehabilitation process. A prototype was manufactured and its mobility was validated using a mannequin.